CHARACTERISTICS OF PRIMARY GLAUCOMA AT BALI MANDARA EYE HOSPITAL PERIOD JANUARY 1, 2018 - DECEMBER 31, 2018 - Sanjiwani, Nyoman Astri Dewi; Triningrat, Anak Agung Mas Putrawati; Jayanegara, I Wayan Gede; Juliari, I Gusti Ayu Made (E-Jurnal Medika Udayana; Vol 10 No 4 (2021): Vol 10 No 04(2021): E-Jurnal Medika UdayanaDO - 10.24843/MU.2021.V10.i4.P07, 2021)
Background : Glaucoma is a group of optic neuropathies characterized by progressive degeneration of ganglion cells in the retina irreversibly causing cupping of the optic disc and causing vision loss. Considering glaucoma as the second cause of blindness after cataracts in the world and its irreversible nature, so this study was conducted to find out the characteristics of glaucoma, especially primary glaucoma at Bali Mandara Eye Hospital period January 1, 2018- December 31, 2018. Methods : This research is a retrospective descriptive study using medical record data. The sampling technique of this research is total sampling. The data obtained according to the inclusion and exclusion criteria were 41 data which were then analyzed using SPSS version 25. Results: This study showed that 38.1% of patients were in the 51-60 years age group. Most of the patients were male (54.8%). The majority live in the Denpasar area (21.4%). POAG was the most common type of primary glaucoma (78.6%). As many as 54.8% of patients experienced an increase in IOP. The majority of patients experienced thinning of the RNFL both in the right eye (61.0%) and the left eye (58.5%). The patient's CDR in the left (35.1%) and right (48.8%) eyes were in a severe state (?0.8). A total of 18 patients (43.9%) suggested to perform central 10-2 treshold test both in right and left eyes. Conclusion: most of the characteristics of primary glaucoma at Bali Mandara Eye Hospital were between 51-60 years old, male, residing in Denpasar, POAG type, and came in advanced clinical appearance. Keywords : characteristics, primary glaucoma, Bali Mandara Eye Hospital.